Superelastic and hydrophobic‐oleophilic modified melamine foam by ultralow amount of graphene for oil/water separation. Issue 11 (9th October 2020) - Zhang, Linjiong; Feng, Lianfang; Gu, Xueping; Zhang, Cailiang
Abstract: Oil spills and organic chemical leakage have caused serious environmental problems, calling for highly effective adsorbents at low cost. Superelastic and hydrophobic‐oleophilic modified melamine foams with ultralow amounts of well‐dispersed graphene were prepared via dip‐coating. The composite foams showed high selectivity for adsorbing various organic chemicals from water and could be regenerated easily. Moreover, excellent adsorption capacity ranging from 80 to 170 times its own weight was found depending on the density of organic chemicals. These coated foams show great potential for continuous oil/water separation and oil fume removal. Abstract :